Effect of tyrosine kinase inhibitors on cell migration and epithelial‐to‐mesenchymal transition in Asian head and neck cancer cell lines. (17th August 2021) - Thwe, Aye Myat; Mossey, Peter; Ellis, Ian R.
Abstract: Background: We investigated the role of epidermal growth factor (EGF) and transforming growth factor α (TGFα) on Asian head and neck cancer patient cell lines; in terms of epithelial‐to‐mesenchymal transition (EMT) and cell migration to determine whether these changes could be reversed using tyrosine kinase inhibitors (Gefitinib and Erlotinib). Methods: Cell migration, protrusion and EMT were assessed using both Scatter assay and Scratch assay. Protein expression and localisation were evaluated using immunofluorescence, SDS‐PAGE and Western blotting techniques to identify the involvement of phosphorylated MAPK (Thr202/Tyr204), phosphorylated EGFR (Y1068) and phosphorylated AKT (Ser473) protein expression. Results: EGF and TGFα induced an EMT‐like phenotypical change, cellular protrusion and cell migration while Gefitinib and Erlotinib blocked these morphological changes and cell migration. We also examined the effect of EGF/TGF α± tyrosine kinase inhibitors on phosphorylation sites Y1068 of epidermal growth factor receptor (EGFR). Y1068 was phosphorylated in all test conditions, and all tested concentrations of inhibitors did not inhibit Y1068 phosphorylation. EGF and TGFα increased phosphorylation of MAPK (Thr202/Tyr204) residues compared with serum‐free control while a one‐hour pre‐treatment with tyrosine kinase inhibitor(s) before addition of growth factors completely blocked this phosphorylation. Phosphorylation of Akt Ser 473 was also induced by EGF and TGFα, and a one‐hour pre‐treatment with the tyrosine kinas inhibitor(s) reduced this phosphorylation. Conclusion: These data suggest that Gefitinib and Erlotinib prevent activation of downstream signalling proteins MAPK (Thr202/Tyr204) and Akt (Ser473) thereby blocking phenotypic change and cell migration. This study supports the potential therapeutic value of Gefitinib and Erlotinib in targeting head and neck cancer.